Development and application of novel measures of foregut lamina propria in Atlantic salmon given 5 different diets - Strating-Gullaksen, Carolien Heleen (The University of Bergen, 2021)
The trial was composed of five diets: a fishmeal/fish oil diet, a 20% soybean meal/30% fishmeal & fish oil diet, a fishmeal/rapeseed oil diet, plant protein concentrates/fish oil diet, plant protein ingredients/mix of rapeseed oil & fish oil diet. Atlantic salmon (Salmo salar) was used as experiment species. Traditional histological approaches are not comparable between different organs and/or treatments, mucosal mapping using universally applicable measures is standardised and can compare different organs and treatments in an unbiased manner. Sectional orientation is of great importance for traditional histological approaches, for mucosal mapping the orientation has no effect. Master's Thesis in Biology BIO399 MAMN-BIO MAMN-HAVSJ